Synthesis of dry SmCl3 from Sm2O3 revisited. Implications for the encapsulation of samarium compounds into carbon nanotubes. (25th September 2016) - Martincic, Markus; Frontera, Carlos; Pach, Elzbieta; Ballesteros, Belén; Tobias, Gerard
Graphical abstract: We report on a simple, fast and economic method that allows the synthesis of anhydrous samarium(III) chloride, as confirmed by synchrotron X-ray beam diffraction of the product. The as-synthesized SmCl3 can be filled inside carbon nanotubes in a high yield, having implications in the biomedical field. Abstract: Samarium is a rare-earth metal with several applications in materials science. It is used in organic chemistry as a reducing agent and it is the active payload in samarium-153 lexidronam, a drug being used for palliative treatment of bone metastases. Recently, the encapsulation of samarium compounds into the cavities of carbon nanotubes has attracted interest for the development of the next generation of radiopharmaceuticals. In the present study, we explore different routes to afford the encapsulation of samarium based materials into single-walled carbon nanotubes. Anhydrous samarium(III) chloride, despite being highly hygroscopic, raises as an excellent candidate to achieve a high filling efficiency. We provide a protocol that allows the synthesis of anhydrous samarium(III) chloride starting from samarium(III) oxide in a fast and simple manner. Synchrotron X-ray powder diffraction confirmed the crystallinity and purity of the synthesized SmCl3 .